Crisis and Disaster in Japan and New Zealand Actors, Victims and Ramifications - Bouterey, Susan; Marceau, Lawrence E. (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This collection examines a broad spectrum of natural and human-made disasters that have occurred in Japan and New Zealand, including WWII and the atomic bombing of Japan and two recent major earthquake events, the Great East Japan Earthquake and the Christchurch Earthquake, which occurred in 2011. Through these studies, the book provides important insights into the events themselves and their tragic effects, but most significantly a multidisciplinary take on the different cultural responses to disaster, changing memories of disasters over time, the impacts of disaster on different societies, and the challenges post-disaster in reviving communities and traditional cultural practices. Bringing in humanities and social science perspectives to disaster studies, this collection offers a significant contribution to disaster studies.